2004
DOI: 10.1016/j.joca.2003.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance evaluation of the interrelationship between articular cartilage and trabecular bone of the osteoarthritic knee11This work is supported by NIH grant RO1 AR 46905 & AG 17762.

Abstract: Degradation of articular cartilage within a compartment correlates with a loss of bone structure in the opposite compartment. The correlation between the (L-M) differences corroborates this relationship. Malalignment of the knee due to cartilage degeneration is associated with bone formation in the diseased condyle and bone resorption in the opposite compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 44 publications
6
64
1
Order By: Relevance
“…If ZOL treatment is initiated at this stage, abnormalities in subchondral bone can be reversed to a large extent and then cartilage degeneration would be retarded accordingly. Conversely, at an advanced stage, subchondral bone accretion was increased mainly due to excessive mechanical stress [30][31][32] . If ZOL therapy is given at this stage, subchondral bone remodeling would not be reversible, and articular cartilage degeneration would continue.…”
Section: Discussionmentioning
confidence: 99%
“…If ZOL treatment is initiated at this stage, abnormalities in subchondral bone can be reversed to a large extent and then cartilage degeneration would be retarded accordingly. Conversely, at an advanced stage, subchondral bone accretion was increased mainly due to excessive mechanical stress [30][31][32] . If ZOL therapy is given at this stage, subchondral bone remodeling would not be reversible, and articular cartilage degeneration would continue.…”
Section: Discussionmentioning
confidence: 99%
“…This group also demonstrated substantially lower vBMD at the 2% level in half the subregions. It has been surmised that lower bone density beneath the lateral compartment may simply represent disuse osteopenia (4,47). This could be due to the fact that more of the load is shifted to the medial compartment due to increasing varus malalignment and joint changes as the disease progresses (17,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies have correlated cartilage volume loss with increased bone volume fraction beneath the affected compartment, and decreased bone volume fraction beneath the unaffected compartment (4,10,11). Fractal signature analysis of macroradiographs has shown thinning of vertical trabeculae, in particular, to be characteristic of the predominantly less dense subchondral trabecular bone in OA (5,12,13).…”
mentioning
confidence: 99%
“…Owing to its lack of radiation and cross-sectional nature, however, high resolution MRI is a more promising tool in assessing bone structure non-invasively, but obtaining images in vivo with a suitable spatial resolution is still challenging. Previous investigations have used 1.5 T scanners combined with surface coils dedicated for high resolution imaging for that purpose (8,13,207) and have studied the knee using high-resolution 3D gradient echo sequences. Axial fast gradient echo sequences were used with an echo (TE) of 4.5 ms, a repetition time (TR) of 30 ms, a flip angle (FA) ¼ 408, a field of view of 10 cm and a matrix size of 512  384 pixels corresponding to a reconstructed spatial resolution of 0.195 mm  0.195 mm.…”
Section: Quantitative Measurement Of Bone Structure In Oa Hardware Anmentioning
confidence: 99%
“…Lindsey et al (207) analyzed the interrelationship of cartilage volume and trabecular bone structure in the knees of 21 healthy volunteers and 53 patients with varying degrees of OA. They found that articular cartilage thinning was associated with loss of bone structure in the opposite femoral condyle (P < 0.05).…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%